Extreme thermophilic condition: An alternative for long-term biohydrogen production from sugarcane vinasse. (30th August 2019) - Niz, M.Y.K.; Etchelet, I.; Fuentes, L.; Etchebehere, C.; Zaiat, M.
Abstract: Boosted by the high temperatures in which vinasse is generated (90 °C–100 °C), this study evaluated the effect of an extreme thermophilic condition (70 °C) on sugarcane vinasse Dark Fermentation (DF) in an Anaerobic Structured Bed Reactor (ASTBR). Four hydraulic retention times (HRT) (19, 15, 12 and 8 h) were evaluated. Higher HRT resulted in a greater H2 production rate (690 mLH2 .d −1 .L −1 ), higher yields (1.8 molH2 .molGlucose −1 ) and greater stability. The extreme temperature inhibits microorganisms' extracellular polymer production, thus leading to a disperse growth, preventing excess biomass accumulation, which was previously reported as the main drawback in H2 production at lower temperatures. The ASTBR higher void index is also responsible for lower biomass/solids retention. The H2 production main route was through the lactic/acetic acid pathway, which is highly reliant on the pH of fermentation broth. The main genus involved in H2 production at 70 °C were Clostridium, Pectinatus, Megasphaera and Lactobacillus. Highlights: Extreme temperature enabled long term H2 production in sugarcane vinasse fermentation. Comparatively to lower temperature, H2 yields four times higher were observed at 70 °C. Lactic/acetic pathway was the main route for H2 production with sugarcane vinasse. At appropriate pH, lactic acid bacteria are beneficial to biological H2 production.